Thermodynamic cycles for renewable energy technologies - Subramanian, K. R. V; George, Raji; P.B, Nagaraj; K, Lokesha; K, Ravi kumar; K S, Reddy; Sankannavar, Ravi; RNR, Shaw; A, Sarkar; G.M, Madhu (IOP series in renewable and sustainable power, 2021)
This research and reference text surveys the role of specialised thermodynamic cycles in renewable energy technologies. The latest innovations in the technology of the Rankine, Stirling, Brayton, Kalina, Goswami and OTEC Rankine cycles are analysed.